Replicative DNA polymerase epsilon and delta holoenzymes show wide-ranging inhibition at G-quadruplexes in the human genome - Hile, Suzanne E; Weissensteiner, Matthias H; Pytko, Kara G; Dahl, Joseph; Kejnovsky, Eduard; Kejnovská, Iva; Hedglin, Mark; Georgakopoulos-Soares, Ilias; Makova, Kateryna D; Eckert, Kristin A (Nucleic acids research, 2025)
G-quadruplexes (G4s) are functional elements of the human genome, some of which inhibit DNA replication. We investigated replication of G4s within highly abundant microsatellite (GGGA, GGGT) and transposable element (L1 and SVA) sequences. We found that genome-wide, numerous motifs are located preferentially on the replication leading strand and the transcribed strand templates. We directly tested replicative polymerase ϵ and δ holoenzyme inhibition at these G4s, compared to low abundant motifs. For all G4s, DNA synthesis inhibition was higher on the G-rich than C-rich strand or control sequence. No single G4 was an absolute block for either holoenzyme; however, the inhibitory potential varied over an order of magnitude. Biophysical analyses showed the motifs form varying topologies, but replicative polymerase inhibition did not correlate with a specific G4 structure. Addition of the G4 stabilizer pyridostatin severely inhibited forward polymerase synthesis specifically on the G-rich strand, enhancing G/C strand asynchrony. Our results reveal that replicative polymerase inhibition at every G4 examined is distinct, causing complementary strand synthesis to become asynchronous, which could contribute to slowed fork elongation. Altogether, we provide critical information regarding how replicative eukaryotic holoenzymes navigate synthesis through G4s naturally occurring thousands of times in functional regions of the human genome.
Keywords: DNA Polymerase II; proteiny vázající poly-ADP-ribosu; genom lidský; Picolinic Acids; Aminoquinolines; DNA; mikrosatelitní repetice; DNA Replication; replikace DNA; aminochinoliny; Genome, Human; Microsatellite Repeats; Holoenzymes; kyseliny pikolinové; G-kvadruplexy; Humans; DNA-polymerasa II; DNA-polymerasa III; holoenzymy; Poly-ADP-Ribose Binding Proteins; DNA Polymerase III; G-Quadruplexes; lidé